THE NATURE OF THE TEXT OF THE CHESTER-BEATTY PAPYRUS IN ACTS - Tasker, R. V. G. (The journal of theological studies, 1937)
R. V. G. TASKER; THE NATURE OF THE TEXT OF THE CHESTER-BEATTY PAPYRUS IN ACTS, The Journal of Theological Studies, Volume os-XXXVIII, Issue 152, 1 October 1937,